PELUANG ADOPSI SISTEM AGROFORESTRY DAN KONTRIBUSI EKONOMI PADA BERBAGAI POLA TANAM HUTAN RAKYAT DI KABUPATEN CIAMIS - Achmad, Budiman; Purwanto, Ris Hadi (Bumi Lestari, 2014)
Agroforestry system as well as the potential species and the corresponding economic values in Ciamis District are very diverse. To encourage farmers adopt agroforestry system, both economical and environmental advantages have to be promoted.  This research was conducted at April to July 2010 at Ciomas, Kalijaya and Kertaharja villages in the Panjalu, Banjarsari, and Cimerak sub-Districts respectively.  Primary and secondary data were analyzed by quantitative and qualitative descriptive.  The result showed that the higher topography, the more simple agroforestry system applied.  The narrower forest size managed (strata 3), the higher chance agroforestry system adopted by farmers.  Farmers in the high and low topography (Northern and Southern Ciamis regions) had higher chance to adopt agroforestry system, while the moderate topography showed lower adoption chance.  The economic contribution of non-forest products (NFPs) influences strongly the farmer decision to adopt agroforestry system. The highest economic contribution of Paraserienthes moluccana was 42.71% in Kalijaya, while the highest economic contribution of non-forest product was 75.00 % in Ciomas.
Keywords: agroforestry, strata, adoption, economic contribution.